Komparasi Bioplastik Berbasis Pati sagu (Genus Metroxxlen,SP) dengan Plastisizer Glyserol dari Minyak Jelantah Melalui Proses Esterifikasi - Nisah, Khairun (Al-Kimia, 2020)
The results of Esterification of waste frying oil is used in this study as bioplastic plasticizers. Sago plate (Genus Metroxxlen, SP), as bioplastic matrix due to amylopectin content. This study intend to utilize waste frying oil and increase the benefits of sago as a bioplastic. The method of making bioplastics by heating 600 C. Characteristics are carried out based on the properties of mechanical properties (Tensile strength), morphology (organoleptic), functional groups (FT-IR), transparasi (UV-VIS), water resistance, and degradation. The composition made, from sago and glycerol (0.5: 1; 1: 1; 0.5: 2; 0.5: 3) produced the best bioplastic with sago composition and glycerol is 0.5: 3. Characteristics that It was observed in the form of elongation of 4.10%, tensile strength 7.08 Kgf / m2, water resistance 0.0037%, transparency of 0.086%, functional groups with absorption in the area of 2924.5 cm-1 which showed alkane compounds, namely streching CH in the area of 2850-3000 cm-1. Streching -O- ether is at 1639.05 cm-1, then the absorption at 3290.86 cm-1 is the -OH functional group absorption. Degradation on day 15 shows a greater decay yield of 34.68 mg. Surface morphology that is not smooth, due to the presence of pores and cracks, this situation is possible due to the lack of OH content in glycerol from used cooking oil.